Pengaruh Citra Merek dan Harga Terhadap Keputusan Pembelian Konsumen Kopi Kenangan - Irma Irma; Revita Mariska; Naila Riska Rahmadani; Syarifah Najlaa Az Zahrah; Annisa Husnul Khotimah; Margareth Henrika; Lusiana Desy Ariswati (Ekopedia: Jurnal Ilmiah Ekonomi, 2026)
This study aims to analyze the effect of brand image and price on the purchasing decisions of Kopi Kenangan consumers in Samarinda City. The research employed a quantitative approach with a causal associative method. Data were collected through the distribution of Likert-scale questionnaires to 100 respondents selected via purposive sampling technique. The data analysis technique used was multiple linear regression analysis, preceded by classical assumption tests including normality and multicollinearity tests using SPSS. The results of the classical assumption test showed that the residual data were normally distributed (Monte Carlo Sig. = 0.490) and free from multicollinearity. The partial hypothesis test (t-test) revealed a surprising finding: brand image had no significant effect on purchasing decisions (Sig. = 0.332). Conversely, price exerted a positive and highly significant effect on purchasing decisions (Sig. < 0.001) and acted as the dominant driver. Simultaneously (F-test), brand image and price significantly influenced purchasing decisions (Sig. < 0.001) with a coefficient of determination (R2) of 0.401. This study concludes that for the undergraduate student segment, economic rationality regarding price overrides brand prestige when making purchasing decisions.